Factors affecting fishermen’s intention to support the newly proposed Marine Protected Area (MPA) in Malacca - Ahmad Sufi, Ayu Naqibah; Matthew, Nitanan Koshy; Wee, Soon Nee; Nik Ab Rahim, Nik Nor Rahimah; Ya'cob, Mohd Rusli (Malaysian Nature Society, 2024)
It is crucial to comprehend the factors influencing fishermen's support for a newly established Marine Protected Area (MPA) in Malacca. This understanding aids in calculating stakeholder perspectives and informs decision-making processes related to marine management. The research objectives were to identify fishermen's perception towards the newly proposed MPA in Malacca and determine the factors affecting their intention to support it. A total of one hundred fifty respondents were enlisted through a questionnaire that specifically targeted the fishermen in the Jasin area of Malacca, who were primarily affected by the gazettement of the MPA. The selection of respondents from nine fishermen bases was via stratified random sampling technique. The theory of planned behaviour (TPB) formed the foundation for comprehending the fishermen's intention to provide support. The factors were specifically mentioned. The outcome proved advantageous for the Department of Marine Parks Malaysia in comprehending the fishermen's perception and, consequently, making suitable decisions regarding the well-being of the impacted fishermen.